Education and Training at the Mekteb-i Bahriye (Naval Academy) During the Reign of Abdülhamid II in Light of the Naval Military Schools Regulations - Muhammet Sebahattin Kurtaran (Yakın Dönem Türkiye Araştırmaları)
Mekteb-i Bahriye (The Naval Academy) played a pivotal role in the modernization of military maritime education and school organization within the Ottoman Empire. By the late 19th century, the institution had accumulated over a century of experience in maritime education since its establishment. This articleexamines the educational system and administrative operations of Mekteb-i Bahriye during the reign of Abdülhamid II, spanning the transition from the 19th to the 20th century, within the framework of the Mekâtib-i Askeriye-i Bahriye (Naval Military Schools) Regulation. The study also evaluates the extent to which the rules outlined in these regulations were implemented, based on archival documents from the period. Additionally, the article seeks to analyze the profiles of the teaching staff, the educational backgrounds of the students, their geographic origins within the Ottoman Empire, and the professions of their fathers, drawing on data from contemporary documents to contextualize the era in which the regulations were applied.